Riwayat Hidup Abu Al-Hassan Al-Asy'ari: Tokoh Ilmu Kalam (260 - 324 H) - Awang Kechik, Ab. Aziz (Jurnal Usuluddin, 1995)
Abu al-Hassan al-Ashaari, who founded a school; a mazhab of ilmu Kalam which later came to be associated with his name, Mazhab al-Ashaari, received his education in tafsir, hadith and fiqh from the Sunni scholars but for aqidah he learned it from his step-father, Abu Ali al-Jubbai, a prominent scholar from the school of al-Muktazilah. Al-Ashaari became well absorbed in the school and was regarded as its important figure and on several occassions used to represent the school in debates and discussions. Latter, al-Ashaari realised that the aqidah of the al-Muktazilah was not in line with the genuine teaching of Islam and this made him conceive another school of thought which was called mazhab Ahl al-Sunnah wa al-Jamaah which he used it as a platform to attack al-Muktazilah which regarded thought as primary with regard to al-Quran and al-Hadith. The conception of al-Ashaari was that al-Quran and al-Hadith were the main sources of reference of aqidah and thought was a neccessity which play a significant role in concretising the argument that had been made in al-Quran and al-Hadith. This article will look into the biography of Abu al-Hassan al-Ashaari, the scholars of ahl al- Sunnah wa al-Jamaah.